All Shari'a is Local: Islam and Democracy in Practice in Northern Nigeria - Kendhammer, Brandon (The review of faith & international affairs, 2017)
Arguably, one of the most important developments across the Muslim world during the past 25 years is the growing evidence of popular support for both democratic government and a wide range of state-sponsored projects of Islamic revivalism, including the enshrinement and implementation of shari'a (Islamic law). But how do Muslims understand the relationship between the two in practice? Focused on the case of northern Nigeria, this article argues that theology matters less than lived, shared community experiences in defining the relationship between Islam and democracy in new and uncertain Muslim-majority democracies. An earlier version of this research was presented in the Religion and World Affairs Series, a project organized and hosted by the Institute on Culture, Religion, and World Affairs (CURA) at Boston University and funded by the Henry Luce Foundation.